PELATIHAN PENDIDIKAN DASAR ORGANISASI BAGI DEWAN MAHASISWA POSKO PERJUANGAN RAKYAT (DPD DEMA POSPERA SUMSEL) SUMATERA SELATAN - Muhammad Iqbal (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
Vocational tertiary institutions are responsible for equipping students with values according to the needs of the world of work and industry. In order to be able to work according to the needs of the world of work, in addition to mastering hard skills, also learning soft skills, at the higher education level in character building it is necessary to provide adequate knowledge and education through student organizations. understand the campus program and environment and become a separate motivation for developing human resource/student competencies. This Community Service activity occurred at the People's Struggle Student Council Pondok. This educational activity was held on 12-13 November 2022. The target audience for this community service activity was active students of the organization. The results obtained are that it is known that there are still those who do not know about organizational leadership and management evaluation through pretest and posttest. The implementation of educational activities related to organizational leadership and management adds to students' knowledge regarding organizational leadership and management.